Effect Nitrobacter with Different Dosage of Water Quality Parameters for Maintenance Media of North African Catfish (Clarias gariepinus) - Alif Saputra; Saberina Hasibuan; Syafriadiman Syafriadiman (Jurnal Perikanan dan Kelautan, 2024)
North African catfish (Clarias gariepinus) is a food ingredient with high protein content, so it is needed as a source of nutrition. In intensive catfish farming activities, there are constraints on water quality. The high stocking density causes a high value of ammonia. In addition, Nitrobacter, in an intensive aquaculture system, is expected to improve water quality. Especially ammonia, so that it can increase the growth and survival of fish. This study aims to determine the effect of Nitrobacter with different doses on the maintenance of North African catfish. This research was conducted from September to October 2022 at the Aquaculture Environmental Quality Laboratory, Department of Aquaculture, Faculty of Fisheries and Marine, Universitas Riau, Pekanbaru. The research method used in this study was a completely randomized design (CRD) 1 factor with five treatment levels and three replications. The treatment in this research is P0: Dosage Nitrobacter 0 mL/L, P1: Dosage Nitrobacter 0.5 mL/L, P2: 1 mL/L, P3: 1.5 mL/L, and P4: 2 mL/L. Giving Nitrobacter is done once a week according to the dose of each treatment. This research was conducted for 30 days. The research results show that dosing Nitrobacter has different effects on reducing ammonia levels and maintaining North African catfish. The best treatment was P3 1.5 mL/L with the smallest ammonia content of 0.0403 mg/L. a specific growth rate of 0.98%. An absolute growth rate of 0.76 g, an absolute length of 1.06 cm, and a survival rate of 81.4%. The value of water quality during the research was 29-300C, pH 6.5-7.0, and DO 2.9-3.3 mg/L. The value of water quality during the study was good enough to support the survival of North African catfish.